2017
DOI: 10.1089/jayao.2017.0024
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in 20-Year Cardiovascular Mortality Risk Among Childhood and Young Adult Cancer Survivors

Abstract: Black survivors of childhood or young adulthood cancers have a higher risk of CVD mortality compared to Whites that varies by cancer type. Knowledge of at-risk populations is important to guide surveillance recommendations and behavioral interventions. Further study is needed to understand the etiology of racial differences in CVD mortality in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…In a study of 79,176 AYA patients with cancer diagnosed in California during 1996-2012, the 10-year risk of incident CVD among African-Americans was 1.55 (95% CI: 1.33-1.81) times that among non-Hispanic Whites with adjustment for cancer type (28). Likewise, a prior SEER-based analysis of AYAs diagnosed at ages 15-34 from 1973 to 2011 found a nonsignificant increase in death from CVD among Black survivors compared with White (HR ¼ 1.33; 95% CI: 0.60-2.95), although estimates were imprecise and models did not appear to account for cancer type (29). Results of this study also indicate a higher burden of CVD mortality among non-Hispanic Black AYAs with cancer, but suggest that the magnitude of this disparity may be considerably greater than previously reported.…”
Section: Discussionmentioning
confidence: 95%
“…In a study of 79,176 AYA patients with cancer diagnosed in California during 1996-2012, the 10-year risk of incident CVD among African-Americans was 1.55 (95% CI: 1.33-1.81) times that among non-Hispanic Whites with adjustment for cancer type (28). Likewise, a prior SEER-based analysis of AYAs diagnosed at ages 15-34 from 1973 to 2011 found a nonsignificant increase in death from CVD among Black survivors compared with White (HR ¼ 1.33; 95% CI: 0.60-2.95), although estimates were imprecise and models did not appear to account for cancer type (29). Results of this study also indicate a higher burden of CVD mortality among non-Hispanic Black AYAs with cancer, but suggest that the magnitude of this disparity may be considerably greater than previously reported.…”
Section: Discussionmentioning
confidence: 95%
“…When socioeconomic risk factors were investigated, Black AYAs with any type of cancer had a higher risk of death from any cause (HR:1.9, 95% CI:1.8–2.0) [ 75 ] overall and specifically after HL [ 31 , 86 ] and testicular cancer [ 106 ] compared to non-Hispanic Whites. Non-Hispanic Black (HR:1.7; 95% CI:1.1–2.8) [ 81 ] AYA cancer survivors also experienced a greater risk of death from non-cancer causes.…”
Section: Resultsmentioning
confidence: 99%
“…Five articles reported racial/ethnic disparities in survival rates (Table 5). Type of survival outcomes assessed for non-Hispanic Black survivors included all-cause mortality ( 22), allcause mortality including relative and standardized rates (31), subsequent malignancy mortality (22), risk of cardiovascularspecific death (25), and risk of any death (25). Types of survival metrics assessed for Hispanic survivors included allcause standardized mortality rates (31).…”
Section: Disparities In Survival Ratesmentioning
confidence: 99%
“…Specifically, one article found that inclusion of census-tract (i.e., neighborhood-level) SES removed the significance of death hazard for non-Hispanic Black survivors diagnosed with astrocytoma and non-astrocytoma CNS tumor, but not acute myeloid leukemia (30). Another article suggests that the adjustment individual and clinical factors removed the significance of cardiovascular-specific death for non-Hispanic Black survivors (25). However, another article found that disparities in all-cause relative mortality rates remained statistically significant for non-Hispanic Black and Hispanic survivors after adjusting for clinical factors, individual demographic and SES factors, and cardiovascular risk in the modeling (31).…”
Section: Disparities In Survival Ratesmentioning
confidence: 99%
See 1 more Smart Citation